Cruciferous Waste Material from Valuable Resource for Nanoparticle-Based Sensors - Anda Maria Baroi; Radu Claudiu Fierascu; Roxana Ioana Matei (Brazdis); Toma Fistos; Irina Fierascu; Camelia Ungureanu (Proceedings, 2023)
Cruciferous vegetables are part of the Brassicaceae family [...]